Acceptability and screening outcomes for hepatitis B, C and human inmunodeficiency virus using rapid diagnostic tests in patients undergoing outpatient endoscopy - Muñoz, Ana (2024)
Introduction: Human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) infections are a global public health concern. In 2019, there were 295.9 million people with chronic hepatitis B and 57.8 million with HCV, and less than 20% were aware of their status. In 2017, there were 37 million people with HIV, and 75% were diagnosed. Creating accessible screening strategies remains a challenge. The use of rapid diagnostic tests (RDTs) is a cost-effective and simple option. The endoscopy unit is an ideal setting due to its high patient flow and qualified personnel. Objective: To evaluate the use and acceptance of two RDTs for detecting HIV, HBV, and HCV in patients undergoing endoscopic examination and to determine the percentage of refusal to undergo testing. Materials and methods: An observational cross-sectional pilot study was conducted. Adults entering two Endoscopy Centers in Santiago were enrolled for outpatient endoscopic examination and were administered two RDTs: Montebio and HCV/HBsAg/HIV Rapid Test after counseling and informed consent. Results: 358 out of 375 patients (96%) accepted the test. 79% were female. The average age was 50±17 years. One subject tested positive for HCV in both tests (0.27%). There were no positive results for HBV/HIV. 17 patients (4.2%) declined the test. The refusal rate by gender was 8.8% (male) vs. 2.7% (female) (p=0.009). The overall experience was positive, and 98% would recommend the process. Conclusions: The use of RDTs in endoscopy represents an opportunity for systematic detection of infected patients with a high level of acceptance.